Rákóczi 1704. évi bácskai hadjáratának földrajzi kérdései - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2011)
Rákóczi’s War for Independence played a significant role in the history of the Hungarian nation and it is one of the better treated part of Hungarian military history. Despite the abundant literature and the rich sources published in vast volumes of the Rákóczianum Archives we cannot entirely know the events of the War for Independence. The campaign against the Raci of prince Francis II Rákóczi in 1704 is among the unprocessed or partially processed military operations and seems insignificant between operations taking place at the same time. The fact that the campaign was led by the prince himself suggests that he attached great importance to it. The Backa operation lacked of major battles but had consequences. The already poisoned Hungarian-Serbian conflict had deepened because the kuruc troops intervened against the Serbian civilian population. As a result, Rákóczi’s War for Independence was accompanied by mutual atrocities. It is a military-geographical interest that the decision made by the kuruc political and military leadership about the Raci campaign contradicts to all military professional knowledge. That is why the campaign did not help to resolve the Raci issue and also played a significant role in the failure of kuruc troops to get the first opportunity to break away from the Carpathian Basin and quickly finish the war. The study presents the strategic relations of the Carpathian Basin and European theatre of operations in the summer of 1704 based on the geographical picture of the country. On this basis gives a picture of II Rákóczi’s Backa campaign and defines those factors of art of war that determined the mutual atrocities.